Pengembangan Video Animasi Berbasis Inquiry Learning Tema Lingkunganku Untuk Melatih Kemampuan Berpikir Kreatif Siswa Kelas VII - Khofifah, Ida; Nulhakim, Lukman; Resti, Vica Dian Aprelia (UNIB Press, 2025)
The uniformity of student responses, which tends to indicate convergent thinking or mere knowledge reproduction, warrants attention as it reveals the students' cognitive process.Therefore, learning media that can stimulate students' creative thinking processes more optimally are needed. This study aimed to obtain data and describe the efficiency level of inquiry learning-based animated videos with the theme